Removal of microorganisms and antibiotic resistance genes from treated urban wastewater: a comparison between aluminium sulphate and tannin coagulants - Grehs, Bárbara W. N. (2019)
The presence of antibiotic resistant-bacteria (ARB) and antibiotic resistance genes (ARG) in treated effluents of urban wastewater treatment plants (WWTP) may represent a threat to the environment and public health. Therefore, cost-effective technologies contributing to minimize loads of these contaminants in the final effluents of WWTP are required. This study aimed at assessing the capacity of coagulation to reduce the ARB&ARG load in secondary treated urban wastewater (STWW), as well as the impact of the process on the structure and diversity of the bacterial community. Coagulation performance using aluminium sulphate, a synthetic substance, and tannins, a biowaste, was compared. Samples were analysed immediately before (STWW) and after the coagulation treatment (Alu, Tan), as well as after 3-days storage in the dark at room temperature (RSTWW, RAlu, RTan), to assess possible reactivation events. Both coagulants decreased the turbidity and colour and reduced the bacterial load (16S rRNA gene copy number, total heterotrophs (HET), and ARB (faecal coliforms resistant to amoxicillin (FC/AMX) or ciprofloxacin (FC/CIP) up to 1–2 log immediately after the treatment. Both coagulants reduced the load of intl1, but in average, aluminium sulphate was able to decrease the content of the analysed ARGs (blaTEM and qnrS) to lower levels than tannin. Reactivation after storage was observed mainly in RTan. In these samples the load of the culturable populations and qnrS gene prevalence increased, sometimes to values higher than those found in the initial wastewater. Reactivation was also characterized by an increment in Gammaproteobacteria relative abundance in the bacterial community, although with distinct patterns for RTan and RAlu. Curvibacter, Undibacterium and Aquaspirillum were among the most abundant genera in RAlu and Aeromonas, Pseudomonas and Stenotrophomonas in RTan. These bacterial community shifts were in agreement with the variations in the culturable bacterial counts of HET for RTan and FC/CIP for RAlu. In summary, the overall performance of aluminium sulphate was better than that of tannins in the treatment of treated urban wastewater.